Ficus plants in the Co-management of Hypertension and Erectile dysfunction - Olufunke Florence Ajeigbe; Ganiyu Oboh; Ayokunle Olubode Ademosun (Phytomedicine Plus, 2021)
A common observation with hypertensive patients is the depreciating ability to maintain an erection. The statistics in the occurrence of erectile dysfunction (ED) have recorded a spike owing to intake of anti-hypertensive drugs together with other contributing factors accompanying the development of ED amongst hypertensive patients. There are medication side-effects faced with high blood pressure (HBP) which promotes ED owing to prolonged intake of anti-hypertensive drugs. It is thus reasonable to state that new therapeutic drugs that addresses both ED, HBP and antihypertensive medication will be strategic interventions towards the decline of these conditions by targeting related enzymes and active proteins. Phytomedicinal plants are promising option in managing numerous diseases such as infertility, cardiovascular diseases, diabetes amongst others. Species variants of fig plants (Ficus species) also serve in the management of a wide range of diseases including hypertension and erectile dysfunction as a result of their aphrodisiac and cardio-protective properties owing to their high residual polyphenolic constituents. Hence, the consumption of ficus plants could possibly be beneficial in managing hypertension especially in patients suffering from erectile dysfunction.